The impact of education on therapy in patients with asthma - Monika Jakimiec; Justyna Emeryk-Maksymiuk; Piotr Milanowski; Piotr Kozak; Michał Szczyrek; Janusz Milanowski (Kazimierz Wielki University, 2016)
Asthma is a chronic disease that still causes a serious health, social and economic burden. Despite the growing knowledge concerning the pathomechanism of the disease and the availability of modern therapeutic possibilities, asthma is often still inadequately controlled. Unfortunately, a large group of patients do not comply with medical recommendations. The reasons for this phenomenon are many. Non-compliance and lack of control of disease are often caused by the lack of information on the side of the patients, so it is important to educate them. It is the foundation on which the awareness of the disease is built. Education of patients with asthma is also essential to improve communication and relationship between the physician, the patient and his family, which is crucial to the success of treatment.